Chemistry Poster-Assisted Demonstration to Enhance Generic Science Skills in Redox Reaction Learning: A Quasi-Experimental Study of Grade XII Students - Ni Putu Erika Pebriana; Eka Junaidi; Nora Listantia (BIOCHEPHY: Journal of Science Education, 2026)
This study examined the effect of the chemistry poster-assisted demonstration method on improving students' generic science skills in redox reaction material. The study was motivated by the low proportion of students reaching the Minimum Mastery Criteria (MMC) in redox material at SMA Negeri 1 Praya, alongside the limited use of instructional methods that present chemical phenomena directly to learners. A quasi-experimental design with a pretest–posttest control group format was employed, involving two Grade XII classes: one received the chemistry poster demonstration treatment, while the other received Discovery Learning combined with lecture-based instruction. The instrument consisted of validated and reliability-tested two-tier multiple-choice items. The mean score of the experimental class increased from 50.57 to 81.37 (moderate-to-high N-Gain), while the control class increased from 62.33 to 73.48 (low N-Gain). A paired-sample t-test produced a significance value (2-tailed) of 0.000 (p < 0.05), leading to the rejection of H? and acceptance of H?. These findings indicate that the chemistry poster-assisted demonstration method has a statistically significant effect on improving students' generic science skills in redox reaction material and may be considered a viable alternative instructional strategy for abstract chemistry topics.